Conceptions of play by children in five countries: towards an understanding of playfulness - Mukherjee, Sarah Jane (2022)
Drawing on a mixed-methods cross-cultural study undertaken in five locations in Argentina, Denmark, Hong Kong, England and the United States in 2018, this paper explores how children (aged five and seven) conceive of playfulness. Following a card-sorting task, 387 children selected familiar activities that they felt were most representative of play and not-play and explained their reasons. The children’s justifications were fully transcribed, and five corpora were created (one per site). Lexicometry was applied, generating sets of the characteristic responses per age in each site. In-depth qualitative interpretation of these modal responses revealed nine dimensions across play and not-play: pleasure, social context, materials, movement, agency, risk, goal, time and focus. Commonalities revealed that children’s ideas around play are not aligned with specific activities but with the sense of agency in a secure physical and social context when carrying out an activity experienced as an end in itself. Implications for playful pedagogies highlight the need to open up play with opportunities for children’s choice and initiative, confident exploration and immersion in the activities in which they participate.